Evaluation of the Service Quality of the Selested Food Stalls in Beslink Collehe of the Philippines: Toward a Guide: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Educational institutes have always been called the second home of students. This is wherethe knowledge is acquired, learned, and practiced. Aside from educational learning, studentsalso get discipline, manners, and skills. Every moment spent in school is considered alesson in itself. Entering school also means leaving the first home in the meantime.However, the needs of the students are being catered to inside the school. Some schoolsalso have food courts where independent food stalls are placed. Considering the school asthe second home, students expect a service that equates to what they experience at theirhomes, including the proper serving of food and cleanliness assurance.The model stated that consumers’ quality perceptions are influenced by a series of fourdistinct gaps. These gaps are on the provider’s side, where the customer’s perception ofservice quality comes from. One hundred college students were randomly selected from theschool and were chosen to answer the Four-point Likert Scale questionnaire, which will bethe instrument to gather data.The data-gathering procedure came to the conclusion that there is a significant relationshipbetween the service quality of selected food stalls and customer satisfaction, given that threedomains significantly influence customer satisfaction. Those three domains are tangibility,reliability, and responsiveness. Also, the respondents perceive all five domains of servicequality (tangibility, assurance, reliability, responsiveness, and empathy) as very satisfactory.Moreover, the p-value of 0.023 is less than the alpha 0.05. Therefore, the Alternativehypothesis is accepted.
Keywords: Business Administration